2007
DOI: 10.1038/sj.jp.7211665
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate and metabolite concentrations in maternal blood, umbilical cord blood, placenta and breast milk

Abstract: Treatment of maternal chronic myeloid leukemia with imatinib mesylate is avoided because of potential fetal effects. Two women with progression of disease during pregnancy required imatinib therapy. Concentrations of imatinib in maternal blood, placenta, umbilical cord blood and breast milk were 886, 2452, 0 to 157, and 596 ng/ml, respectively. Concentrations of the active metabolite CGP74588 in maternal blood, placenta, umbilical cord blood and breast milk were 338, 1462, 0 and 1513 ng/ml, respectively. As Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 17 publications
2
54
0
3
Order By: Relevance
“…6 However, the mechanism of nutrient supply to the fetus varies at different stages in gestation. Prior to 10 weeks, there are no maternal arterial connections with the intervillous space, and during the first few weeks of development it is thought most likely that the embryo obtains nutrients by simple diffusion from blood pooled in the trophoblastic lacunae.…”
Section: Fetal Outcomementioning
confidence: 99%
“…6 However, the mechanism of nutrient supply to the fetus varies at different stages in gestation. Prior to 10 weeks, there are no maternal arterial connections with the intervillous space, and during the first few weeks of development it is thought most likely that the embryo obtains nutrients by simple diffusion from blood pooled in the trophoblastic lacunae.…”
Section: Fetal Outcomementioning
confidence: 99%
“…It has been reported that the concentration of imatinib and its active metabolite were higher in the placenta than in the maternal blood, while they were low or undetected in the umbilical cord. These findings suggest limited placental transfer of imatinib in late pregnancy (Russell et al, 2007). It seems that administering imatinib during the first trimester is associated with a considerable risk of congenital anomalies and spontaneous abortions, while late exposure does not have the same impact.…”
Section: Chronic Leukemia In Pregnancy 521 Chronic Myelogenous Leukmentioning
confidence: 74%
“…592 There is evidence of increased fetal risk, and risk vs benefi t should be considered for use during pregnancy. 596 Animal studies suggest potential teratogenicity. 596 Imatinib can enter breast milk in animals and has been detected in breast milk in humans.…”
Section: -3 Months)mentioning
confidence: 99%
“…596 Animal studies suggest potential teratogenicity. 596 Imatinib can enter breast milk in animals and has been detected in breast milk in humans. 596 3.7.2.3 Monitoring-The manufacturer recommends a CBC count weekly for the fi rst month of therapy, biweekly for the second month, and then periodically.…”
Section: -3 Months)mentioning
confidence: 99%
See 1 more Smart Citation